Nutrient content and uptake of basmati rice as influenced by organic and inorganic sources of nutrients - Yadav, Komal; Yadav, Devideen; Yadav, R.B. (Annals of Agricultural Research, 2017)
Performance of organic sources i.e. vermi-compost (VC), poultry manure (PM), farm yard manure (FYM) in combination with chemical fertilizers and sole chemical fertilizers with 100% recommended dose of fertilizers (RDF) i.e. 120:60:60 NPK kg ha–1 and 125% RDF were evaluated in terms of nutrient content and nutrient uptake of basmati rice at crop research centre of Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, India, during kharif - 2013 using randomized block design (RBD). Results revealed that highest nitrogen, phosphorus and potassium content in grain and straw and their uptake in basmati rice were recorded with application of 125% RDF through inorganic source of nutrient over other treatments. The highest grain (4.56 t ha–1) and straw yield (6.49 t ha–1) was also recorded with 125% RDF through inorganic source of nutrient but it was statistically similar to the treatment containing 50% RDF through inorganic sources + 50% through PM.